Intraoperative 2D C-arm and 3D O-arm in children: a comparative phantom study. (1st October 2018) - Prod'homme, M.; Sans-Merce, M.; Pitteloud, N.; Damet, J.; Lascombes, P.
Abstract: Purpose: Exposure to ionizing radiation is a concern for children during intraoperative imaging. We aimed to assess the radiation exposure to the paediatric patient with 2D and 3D imaging. Methods: To evaluate the radiation exposure, patient absorbed doses to the organs were measured in an anthropomorphic phantom representing a five-year-old child, using thermoluminescent dosimeters. For comparative purposes, organ doses were measured using a C-arm for one minute of fluoroscopy and one acquisition with an O-arm. The cone-beam was centred on the pelvis. Direct and scattered irradiations were measured and compared (Student's t -test). Skin entrance dose rates were also evaluated. Results: All radiation doses were expressed in µGy. Direct radiation doses of pelvic organs were between 631.22 and 1691.87 for the O-arm and between 214.08 and 737.51 for the C-arm, and were not significant (p = 0.07). Close scattered radiation on abdominal organs were between 25.11 and 114.85 for the O-arm and between 8.03 and 55.34 for the C-arm, and were not significant (p = 0.07). Far scattered radiation doses on thorax, neck and head varied from 0.86 to 6.42 for the O-arm and from 0.04 to 3.08 for the C-arm, and were significant (p = 0.02). The dose rate at the skin entrance was 328.58 µGy.s −1 for the O-arm and 1.90 with the C-arm. Conclusion: During imaging of the pelvis, absorbed doses for a 3D O-arm acquisition were higher than with one minute fluoroscopy with the C-arm. Further clinical studies comparing effective doses are needed to assess ionizing risks of the intraoperative imaging systems in children.